2016
DOI: 10.1111/pde.12992
|View full text |Cite
|
Sign up to set email alerts
|

Topical Cidofovir for Recalcitrant Verrucae in Individuals with Severe Combined Immunodeficiency After Hematopoietic Stem Cell Transplantation

Abstract: Verrucae vulgaris in patients with severe combined immunodeficiency (SCID) post-hematopoetic stem cell transplantation (HCST) can be challenging to manage. We describe two brothers with X-linked SCID who both had severe, persistent verrucae that did not respond to traditional topical therapies, including liquid nitrogen, imiquimod, salicylic acid, sinecatechins, 40% urea and 5-fluorourcil. Both brothers had full response to topical 3% cidofovir, which should be considered in recalcitrant warts in post-HSCT SCI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 5 publications
0
10
0
Order By: Relevance
“…Several case reports have been presented for PSV effects on viral warts [23][24][25][26][27] (Table 1) and other HPV-related diseases [28][29][30]. For example, one study found that topical treatment with a sinecatechins 10% ointment thrice daily for three weeks in a 34-year-old man with atopic dermatitis, who had not responded to 5-fluorouracil ointment, water filtered infrared A irradiation, and topical retinoids, resulted in a complete remission of all facial warts within 20 days [23].…”
Section: Case Eeports Of Psv Effects On Viral Warts and Other Hpv-related Diseasesmentioning
confidence: 99%
“…Several case reports have been presented for PSV effects on viral warts [23][24][25][26][27] (Table 1) and other HPV-related diseases [28][29][30]. For example, one study found that topical treatment with a sinecatechins 10% ointment thrice daily for three weeks in a 34-year-old man with atopic dermatitis, who had not responded to 5-fluorouracil ointment, water filtered infrared A irradiation, and topical retinoids, resulted in a complete remission of all facial warts within 20 days [23].…”
Section: Case Eeports Of Psv Effects On Viral Warts and Other Hpv-related Diseasesmentioning
confidence: 99%
“…HSCT can result in prompt eradication, though JAK3 mutations and common γ chain SCID can have significant warts post-HSCT, which may be in part due to poor NK cell function ( 64 ). Topical cidofovir has recently been shown in a case report to be effective in some of these patients ( 72 ). In one case, regression was observed after papillomavirus vaccination ( 61 ).…”
Section: Chronic Viral Skin Infections In Primary Immunodeficiencymentioning
confidence: 99%
“…Preliminary studies have similarly demonstrated efficacy for extragenital warts . The use in children has been limited, with only three reports of treatment with sinecatechins ointment in the literature to date . In two‐thirds of these cases, warts resolved completely after thrice daily use of sinecatechins ointment for 8‐10 weeks.…”
Section: Introductionmentioning
confidence: 99%